Pengaruh Model Pembelajaran Kooperatif Tipe Number Head Together (NHT) dan Motivasi Belajar Terhadap Hasil Belajar Ekonomi pada Siswa Kelas X MAN X Koto Singkarak - Novieza Novieza; Marwan Marwan (Program Magister Pendidikan Ekonomi (S2), 2016)
This study aimed to find and analyze the influence of cooperative learning model number Head Together (NHT) and the motivation to learn the results of the economic study in class X MAN X Koto Singkarak.The population in this study were all students of class X MAN X Koto Singkarak enrolled in the academic year 2014/2015. Sampling in this study using purposive sampling technique, that is by selecting a sample that had been selected based on certain considerations. Selection of experimental class and control class is done at random by using a lottery, where the result is to make the class as a class experiment X.1 and X.2 class as a class controls the number of samples of two classes of 52 students. Data analysis techniques in studies using independent test samples T-test and two-way ANOVA.The results showed: (1). Economics student learning outcomes given the cooperative learning model type Number Head Together (NHT) is significantly higher than the results of the economic study students who are taught by using conventional learning models, (2). Economic learning outcomes of students who have high motivation to learn is significantly higher than the results of the economic study of students who have low motivation, (3). There was no significant interaction between learning models and learning motivation toward economics student learning outcomes.Keywords : Cooperative Learning Model Number Type Head Together (NHT), learning motivation and learning outcomes